Identification of the main contributors to blood culture contamination at a tertiary care academic medical center. Issue 3 (September 2022) - Sacchetti, Brianna; Travis, Justin; Steed, Lisa L.; Webb, Ginny
Summary: Background: Blood culture contamination poses an issue to all hospital systems worldwide because of the associated costs of extended length of stays, unnecessary antibiotic therapy, and additional laboratory testing that are preventable with proper handling and collection techniques. Methods: In our study, multiple units, staff, and collection methods were compared to determine the primary culprits of contamination from a tertiary care academic medical center, which includes a pediatric hospital and both adult and pediatric emergency departments. Results: Over 33 months, 2, 083 out of 88, 322 total blood cultures collected were contaminated, with an overall contamination rate of 2.4%. A moderate positive correlation was found between the monthly total number of cultures and monthly contamination rate ( r = 0.411 P < .01). The most notable factors associated with contamination were found to be phlebotomy teams (2.7%) ( P < .01), peripheral draws (2.3%) ( P <.01), adult emergency departments (2.6%) ( P < .01), and pediatric intensive care units (2.7%) ( P < .01). A positive correlation was present between the number of hospital beds per unit and unit contamination rates ( r = 0.429 P < .01). Conclusion: Our results were used to make recommendations for decreasing the rate of blood culture contamination in this institution, which includes acknowledgement of an overwhelmed staff and mandatory periodic training on acceptable aseptic technique and contamination awareness. Understanding the factors contributing to blood culture contamination can aid efforts to reduce contamination rates.